Identification of fish fromthe seagrass ecosystem, Kampung Madong Waters, Kampung Bugis Village, Tanjungpinang City, Kepulauan Riau Province - Mhd Hapizeldi; ddiwan ddiwan; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractSeagrass ecosystems serve as place for spawning, nursery and feeding grounds of aquatic organisms, including fish. A research aims to identify the types of fish present in the seagrass ecosystems was conducted in March 2019. Samplings were done 4 times, once/ week. The fish were captured using gill nets (1-2 inch mesh size) and net traps (3 inch mesh size). Fish samples were then identified.Resultsshown thatthere were 2,322 fish captured, consisting of42 species, 39 genera, 31 families, 38 orders, and 1 classes.The commonfish are belonged to Siganidae and Carangidae,while the least wasbelonged to Antennariidae and Pomacentridae families. Among the fish captured, 26 species were categorized as consumption fish, 11 species were ornamental fish and 5 species were ornamental-consumption fish.The water quality in the Madong Vilage indicate that: temperature 29-30º C, current speed 0.14-0.15 m/sec,dissolved oxygen6.8-7mg/L,pH7.6-8 and salinity 32-34‰.Keywords: Siganidae, Carangidae,consumption fish, ornamental fish